移植物抗宿主疾病的治疗或预防方法 (2018)
提供了种用于治疗或预防接受了移植(包括造血细胞移植)的主体出现移植物抗宿主疾病(GVHD)的方法。该方法包含在体外令移植物接触有效数量的粘膜瘤病毒，以抑制移植物内T淋巴细胞的增殖或预防受试体移植该移植物后出现移植物抗宿主疾病(GVHD)。在移植物接触粘液瘤病毒后，该方法包含将经过病毒处理的移植物植入到受试体内。 A method of treating or preventing graft versus host disease (GVHD) in a subject receiving a graft comprising hematopoietic cells is provided. The method comprises contacting the graft ex vivo with an amount of a Myxoma Virus effective to inhibit proliferation of T lymphocytes in the graft and to treat or prevent GVHD in the host subject following infusion of the graft into the subject. After the contacting of the graft with the Myxoma Virus, the method comprises transplanting the virus-treated graft into the subject.